1999
DOI: 10.1080/026520399283696
|View full text |Cite
|
Sign up to set email alerts
|

Control of growth and fumonisin B1production by Fusarium verticillioides and Fusarium proliferatum isolates in moist maize with propionate preservatives

Abstract: The effect of propionic acid, its sodium salt or a commercial formulation of propionates (0.03, 0.05 and 0.07%), on growth and fumonisin B1 production by Fusarium verticillioides and F. proliferatum isolated was evaluated on irradiated maize at different water activities (aw, 0.93, 0.95, 0.98) and temperatures (15, 25 degrees C). The four isolates grew at all aw x temperature treatments in the absence of propionates. At the highest propionate concentration tested (0.07%), however, growth was restricted to 0.98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Ochratoxin A production followed the same general behaviors as observed in the growth parameters. Marín et al (1995Marín et al ( , 1999 have demonstrated that water activity interaction is an important factor that influences growth parameter and mycotoxin production when different fungi species grow in presence of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochratoxin A production followed the same general behaviors as observed in the growth parameters. Marín et al (1995Marín et al ( , 1999 have demonstrated that water activity interaction is an important factor that influences growth parameter and mycotoxin production when different fungi species grow in presence of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this, the seeds are often treated with preservatives, such as propionic and sorbic acid and their salts (Arroyo et al, 2005). Marín et al (1999) showed that currently used preservatives are ineffective in controlling mycotoxin production by several fungal species. The use of food grade antioxidants could be an alternative strategy to control ochratoxigenic fungi in peanut seeds.…”
Section: Introductionmentioning
confidence: 99%
“…It is common for farmers to store maize for these long periods depending on sale opportunities and in preparation for unforeseen crop failures that periodically arise in this region. The moisture content of maize at harvesting may be high and therefore conducive to fungal colonization and fungal toxin synthesis by Fusarium species before consumption (Marin et al 1999). Drying reduces these levels, but if this process is delayed, inefficient or absent in the period post-harvest, such fungi can readily colonize the grain where appropriate humidity and temperature allow.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that under these conditions propionic acid is not effective against common bread spoilage organisms [125]. Additionally, a reduction of preservatives to sub-inhibitory levels might stimulate the growth of spoilage molds [126] and/or mycotoxin production [127,128,129]. Recent trends in the bakery industry have included the desire for high-quality foods, which are minimally processed and do not contain chemical preservatives, thus increasing the interest toward natural preservation systems [130].…”
Section: Probiotic Bacteria In the Composition Of Bread Sourdoughmentioning
confidence: 99%